Use Of Interactive Educational Technologies in Teaching Subjects of Molecular Biology Department - Aqida Valikhanova (Genius Journals, 2023)
This article describes how to use interactive educational technologies in teaching the topic of proteins, carbohydrates, lipids and nucleic acids at the Department of Molecular Biology
Keywords: learning effectiveness; interactive educational technologies; brainstorming